2023
DOI: 10.3390/diagnostics13050829
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Computed Tomography Angiography as Imaging Method for Endoleak Classification after Endovascular Aneurysm Repair: A Case Series and Systematic Review of the Literature

Abstract: Introduction: This study evaluated our experience with dynamic computed tomography angiography (dCTA) as a diagnostic tool after endovascular aortic aneurysm repair (EVAR) with respect to the endoleak classification and the available literature. Methods: We reviewed all patients who underwent dCTA because of suspected endoleaks after the EVAR and classified the endoleaks in these patients based on standard CTA (sCTA) and dCTA. We systematically reviewed all available publications that investigated the diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…Endoleaks may be hard to determine even with the use of multiphase CTA. The research group of Fioole showed that dynamic CTA is of added value regarding the detection and classification of slow-flow endoleaks, and especially of type 2 endoleaks which usually originate from backbleeding lumbar arteries [3]. Improvement of the endoleak classification also allows the endovascular specialist to make targeted reinterventions.…”
mentioning
confidence: 99%
“…Endoleaks may be hard to determine even with the use of multiphase CTA. The research group of Fioole showed that dynamic CTA is of added value regarding the detection and classification of slow-flow endoleaks, and especially of type 2 endoleaks which usually originate from backbleeding lumbar arteries [3]. Improvement of the endoleak classification also allows the endovascular specialist to make targeted reinterventions.…”
mentioning
confidence: 99%